2008
DOI: 10.1007/s11009-008-9089-z
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Distortion Risk Measures

Abstract: The current literature does not reach a consensus on which risk measures should be used in practice. Our objective is to give at least a partial solution to this problem. We study properties that a risk measure must satisfy to avoid inadequate portfolio selections. The properties that we propose for risk measures can help avoid the problems observed with popular measures, like Value at Risk (VaR α ) or Conditional VaR α (CVaR α ). This leads to the definition of two new families: complete and adapted risk meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(37 citation statements)
references
References 25 publications
0
34
0
3
Order By: Relevance
“…There are two key elements to define a distortion risk measure: first, the associated distortion function; and, second, the concept of the Choquet (14) Integral. A detailed literature review of distortion risk measures is available in Denuit et al (20) and Balbás et al (6) . The distortion function, Choquet Integral and the distortion risk measure can be defined as follows:…”
Section: Distortion Risk Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…There are two key elements to define a distortion risk measure: first, the associated distortion function; and, second, the concept of the Choquet (14) Integral. A detailed literature review of distortion risk measures is available in Denuit et al (20) and Balbás et al (6) . The distortion function, Choquet Integral and the distortion risk measure can be defined as follows:…”
Section: Distortion Risk Measuresmentioning
confidence: 99%
“…In some situations, coherence of risk measures is a requirement (see, for instance, Cox (15) ) but, nonetheless, some criticisms can be found, for example, in Dhaene et al (23) . Additional properties for distortion risk measures are provided by Jiang (41) and Balbás et al (6) . As shown in the previous section, GlueVaR risk measures may be interpreted as a linear combination of VaR and TVaR risk measures.…”
Section: Subadditivity In the Tailmentioning
confidence: 99%
“…Concavity of the distortion function is the key element to define risk measures that belong to both groups (Wang and Dhaene, 1998). Suggestions on new desirable properties for distortion risk measures are proposed in Balbas et al (2009), while generalizations of this kind of risk measures can be found, among others, in Hürlimann (2006) and Wu and Zhou (2006).…”
Section: Distortion Risk Measuresmentioning
confidence: 99%
“…The distortion risk measure has several useful properties such as positive homogeneity, translation invariance, additivity for comonotonic risks, and monotonicity. For more details, see Denuit et al [13], Dhaene et al [20], and Balbás et al [21]. Several popular risk measures belong to the family of distortion risk measures.…”
Section: Introductionmentioning
confidence: 99%